Religious foundations of Western civilization: Judaism, Christianity, and Islam - Neusner, Jacob (Abingdon Press, 2006)
Defining the terms -- What do we mean by "religion" and "Western civilization"? / William Scott Green -- Religions of the West -- Judaism / Jacob Neusner -- Christianity : what it is and how it defines Western civilization / Bruce Chilton -- Islam : what it is and how it has interacted with Western civilization / Th. Emil Homerin -- Religion, politics, culture, law, and society -- Judaism / Alan J. Avery-Peck -- Christianity / Bruce Chilton -- Islam / Th. Emil Homerin -- Philosophy : Averroes, Maimonides, and Aquinas / Seymour Feldman -- Mysticism as a meeting ground : seeing the unseen / Elliot R. Wolfson -- Historic encounters -- Latin Christianity, the crusades, and the Islamic response / James A. Brundage -- Judaism, Christianity, and Islam in Spain from the eighth to the fifteenth centuries / Olivia Remie Constable -- Christianity and Islam in the Balkans from the fifteenth to the twentieth centuries / Amila Buturovic -- Zionism, imperialism, and nationalism -- Zionism / Jacob Neusner -- Christian imperialism / Bruce Chilton -- Political Islam / Th. Emil Homerin -- Modernity and religion in the West : negotiating change -- The modernization of Christianity / Bruce Chilton -- The modernization of Judaism / Jacob Neusner -- The modernization of Islam / Th. Emil Homerin -- Religion and western civilization in the twenty-first century -- Judaism, Christianity, and Islam in their contemporary encounters -- Judaism addresses Christianity / Jon D. Levenson -- Christianity meets other religions / Bruce Chilton -- Islam and Pluralism / Th. Emil Homerin -- Timeline / compiled by Cory Berry-Whitlock